Optical and Thermal Properties of In2S3 - Faycel Saadallah; Neila Jebbari; Najoua Kammoun; Noureddine Yacoubi (International Journal of Photoenergy)
Photothermal deflection spectroscopy (PDS) is carried out in order to investigate thermal and optical properties of Al doped In2S3. The influence of thermal annealing on its gap energy as well as its thermal properties is revealed. In this way, we notice that thermal conductivity is increased and the gap energy is reduced. These features are probably due to the improvement of the crystalline structure of the sample.